Genevieve Fallon Steefel papers - Steefel, Genevieve Fallon, 1899-1971.
Correspondence, speeches, political bulletins, flyers, announcements, and other campaign material relating to political campaigns of the Progressive Party, especially the 1948 presidential campaign of Henry A. Wallace. Documents her service on the executive board of the Independent Voters of Minnesota. Other organizations represented include the Congress of Industrial Organizations Political Action Committee, National Citizens Political Action Committee, National Wallace for President Committee, Progressive Citizens of America, and Women for Wallace. Includes correspondence of Henry A. Wallace.
Civic leader.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Wallace, Henry A. -- 1888-1965.; Wallace, Henry A. -- 1888-1965 -- Correspondence; Congress of Industrial Organizations (U.S.). -- Political Action Committee; Independent Voters of Minnesota; National Citizens Political Action Committee; National Wallace for President Committee; Progressive Citizens of America; Women for Wallace; Progressive Party (U.S. : 1948); Elections -- United States -- 1948.; Progressivism (United States politics); Minnesota -- Politics and government; Civic leaders